PENDEKATAN KUANTITATIF DAN KUALITATIF DALAM PENELITIAN ILMU SOSIAL: Titik Kesamaan dan Perbedaan - Sermada Kelen Donatus (Litbang STFT Widya Sasana Malang, 2016)
The quantitative and qualitative approach is a scientific method used popularly in the social research operating in the area of social sciences. The author of this article wants to give an insight into the difference of quantitative and qualitative approach, although both of these approaches are utilized in the praxis unseparatedly. The quantitative method is refering to the collection of the empirical data inspired by the philosophy of positivism, whereas the qualitative approach is connected with the understanding and the interpretation expressed by the subject discerning the meaning of the empirical data under the light of the existencial-phenomenological philosophy. The last part of the article contains the possibility of making a unity of the two approaches in social research.